Factor influencing guests’intention to stay at green hotel / Nurul Farseha Ariffin - Ariffin, Nurul Farseha (2020)
The main purpose of this paper is to review on the factor that influencing guests’ intention to stay at green hotel based on the existing news and literature. Generally, there are several factors that influencing guests’ intention may due to eco-friendly attitudes, willingness to pay more and the positive word-of-mouth from guest toward the green hotel. Hence, the researcher attempts to bring the entire concept of factor that influencing guests’ intention to stay in green hotel based on the finding of the previous research, published article, and news.